A Remote Arene-Binding Site on Prostate Specific Membrane Antigen Revealed by Antibody-Recruiting Small Molecules - Zhang, Andrew X. (2010)
Prostate specific membrane antigen (PSMA) is a membrane-bound glutamate carboxypeptidase overexpressed in many forms of prostate cancer. Our laboratory has recently disclosed a class of small molecules, called ARM-Ps (antibody-recruiting molecule targeting prostate cancer) that are capable of enhancing antibody-mediated immune recognition of prostate cancer cells. Interestingly, during the course of these studies, we found ARM-Ps to exhibit extraordinarily high potencies toward PSMA, compared to previously reported inhibitors. Here, we report in-depth biochemical, crystallographic, and computational investigations which elucidate the origin of the observed affinity enhancement. These studies reveal a previously unreported arene-binding site on PSMA, which we believe participates in an aromatic stacking interaction with ARMs. Although this site is composed of only a few amino acid residues, it drastically enhances small molecule binding affinity. These results provide critical insights into the design of PSMA-targeted small molecules for prostate cancer diagnosis and treatment; more broadly, the presence of similar arene-binding sites throughout the proteome could prove widely enabling in the optimization of small-molecule–protein interactions.